'You have to be a bit brave': barriers to Scottish student-teachers' participation in study-abroad programmes. Issue 1 (1st January 2016) - Santoro, Ninetta; Sosu, Edward; Fassetta, Giovanna
Abstract: This article reports on a study that examined Scottish student teachers' attitudes to study-abroad and the reasons underpinning their reluctance to participate in these programmes. Data collection comprised a mixed-methods approach consisting of a survey of 318 student-teachers in one Scottish university followed by semi-structured interviews with 12 volunteers. Descriptive and thematic data analyses revealed that the majority of student-teachers perceived international study experience as useful to their development as teachers. However, their lack of confidence and anxiety about travel were significant reasons about why they did not take up opportunities to study abroad. In particular, fear of not being understood and fear of different cultural norms and practices shaped their decision to remain in Scotland. In order to allay these fears and increase student–teacher participation, the authors suggest universities invest in intercultural competence training, language education and provide detailed briefings as part of the recruitment process into study-abroad programmes.